2013
DOI: 10.1088/1748-3182/8/3/036005
|View full text |Cite
|
Sign up to set email alerts
|

Surface microstructures of daisy florets (Asteraceae) and characterization of their anisotropic wetting

Abstract: The surface microstructures on ray florets of 62 species were characterized and compared with modern phylogenetic data of species affiliation in Asteraceae to determine sculptural patterns and their occurrence in the tribes of Asteraceae. Their wettability was studied to identify structural-induced droplet adhesion, which can be used for the development of artificial surfaces for water harvesting and passive surface water transport. The wettability was characterized by contact angle (CA) and tilt angle measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
1
31
0
2
Order By: Relevance
“…The number of stylar cuticular patterns is higher than that of petal cuticular patterns since the stylar hairs in contrast to petal cells can exhibit a combination of longitudinal and transverse cuticular striae. A crested pattern, which on the stylar hairs is confined to the Onoserideae and Mutisieae, is found on the petals in Mutisieae as well as in Cichorieae, Arctotideae, Calenduleae, and Inuleae (Baagøe 1977a(Baagøe , 1978Koch et al 2013). It is noteworthy that in Gazania (Arctotideae, fig.…”
Section: Comparison With Petal Surfaces In Asteraceaementioning
confidence: 97%
See 4 more Smart Citations
“…The number of stylar cuticular patterns is higher than that of petal cuticular patterns since the stylar hairs in contrast to petal cells can exhibit a combination of longitudinal and transverse cuticular striae. A crested pattern, which on the stylar hairs is confined to the Onoserideae and Mutisieae, is found on the petals in Mutisieae as well as in Cichorieae, Arctotideae, Calenduleae, and Inuleae (Baagøe 1977a(Baagøe , 1978Koch et al 2013). It is noteworthy that in Gazania (Arctotideae, fig.…”
Section: Comparison With Petal Surfaces In Asteraceaementioning
confidence: 97%
“…The cuticular pattern of only longitudinal striae occurs in Senecioneae, Calenduleae, Astereae, Helenieae, Coreopsideae, Heliantheae, and Madieae on the stylar hairs ( fig. 5) as well as on the petal surfaces (Baagøe 1977a(Baagøe , 1977b(Baagøe , 1978Koch et al 2013). However, in the tribes Senecioneae, Calenduleae, and Astereae, the pattern of transverse striae on the petal surfaces (Baagøe 1978;Koch et al 2013) is not found on the stylar hairs.…”
Section: Comparison With Petal Surfaces In Asteraceaementioning
confidence: 99%
See 3 more Smart Citations